PERSEPSI SISWA TERHADAP PEMBELAJARAN SENI TARI DI SMA N 5 SOLOK SELATAN - Dina Permata Sari; Yuliasma Yuliasma; Idawati Syarif (FBS Universitas Negeri Padang, 2013)
Abstract This study aims to identify and describe students’ perceptions towards the learning of dance grade XI SMAN 5 South Solok. This qualitative research used descriptive analysis by describing and analyzing data that were collected through observation, interviews and questionnaires. Subjects of the research were students of grade XI, at first semester SMAN 5 South Solok. There were 5 classes in this grade, they are XI IPA 1, IPA 2, IPS 1, IPS 2, and IPS 3. Object of study was dance subject. The samples in this study were 50 students (25% of the total population). Technique of data analysis was conducted by using percentages. Based data analysis, it was found that students’ perception toward the learning of dance was categorized as poor (20.74%), the perception of students’ want to learning dance was categorized as poor (36.29%), students' perceptions on assessment of dance learning can be categorized as good (66.50%). Based on these findings, it can be concluded that the average percentage of students’ perception towards the learning of dance at SMAN 5 South Solok was 41.17% or it is categorized as poor.